2010
DOI: 10.1590/s0104-11692010000600005
|View full text |Cite
|
Sign up to set email alerts
|

Work in Rotating Shifts and its Effects on the Daily Life of Grain Processing Workers

Abstract: This study aimed to investigate the effects of alternating shift work in the daily life of grain processing workers. A quantitative data collection research was carried out at a grain processing company in Goiás -Brazil. Research participants were 53 alternating shift workers. A questionnaire was developed and used for data collection, based on the principles of chronobiology and Pittsburgh Sleep Quality Index, with 31 closed and one open question.The result showed dissatisfactory sleep quality for approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
3
7
0
9
Order By: Relevance
“…People who sleep poorly tend to have more morbidities, shorter life expectancy, and early aging. 23 In a study, 24 results were similar to those obtained in this study, since the evaluation of the practice of physical activities among the teachers who participated in the study indicated the occurrence of 28.3% (n = 83) of "sedentary" (who do not perform any physical activity for ten continuous minutes in the week). Adding the sedentary to the irregularly active, it was observed that more than half (56.6%) of the teachers participating in the research are not active or sedentary.…”
Section: Discussionsupporting
confidence: 81%
“…People who sleep poorly tend to have more morbidities, shorter life expectancy, and early aging. 23 In a study, 24 results were similar to those obtained in this study, since the evaluation of the practice of physical activities among the teachers who participated in the study indicated the occurrence of 28.3% (n = 83) of "sedentary" (who do not perform any physical activity for ten continuous minutes in the week). Adding the sedentary to the irregularly active, it was observed that more than half (56.6%) of the teachers participating in the research are not active or sedentary.…”
Section: Discussionsupporting
confidence: 81%
“…1,2 Since college, medical students are subjected to a stressful routine. They establish arduous study schemes to achieve an appropriate academic performance.…”
mentioning
confidence: 99%
“…34 Ainda, a organização do trabalho em turnos alternantes pode ser considerada um fator de risco adicional para o desenvolvimento de DCV, 12 por promover maior exposição aos fatores de risco modificáveis para DCV, principalmente a alimentação inadequada e prática de atividade física diminuída. 35 Da mesma forma, contribui com a privação do sono e consequentes alterações no ritmo circadiano, acarretando desequilíbrios hormonais (leptina, grelina, melatonina e cortisol). 11…”
Section: Análises Estatísticasunclassified